EXPLORING THE SCIENTIFIC FRONTIERS OF AI INTEGRATION IN MATHEMATICS EDUCATION - Sulaymanov, Zulqaynar; Mukhammedov, Rofiddin; Aktamov, Bunyod (Science technology&Digital finance, 2023)
This theme encompasses the empirical investigation into the role of Artificial Intelligence (AI) in teaching mathematics, focusing on scientific methodologies to assess the efficacy of personalized learning, measure the impact on critical thinking skills, and understand the scientific principles underpinning the transformative potential of AI in the educational domain. Through rigorous research, the theme aims to contribute to evidence-based practices, fostering a deeper understanding of how AI can advance pedagogical methodologies and promote cognitive development in mathematics education.